PENGARUH MIKORIZA TERHADAP PENYAKIT LAYU FUSARIUM (Fusarium oxysporum) PADA TEMBAKAU (Nicotiana tabacum L.) DALAM MEDIA PASIR KUARSA MENGANDUNG KOMPOS AMB-P0K - Dony Firman Fajariza; Anton Muhibuddin; Antok Wahyu Sektiono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Sand is one of the planting media, but the use of sand as a planting medium is still rare due to the low nutrient content. Quartz sand needs the addition of compost to support plant growth. Mycorrhiza can also be added to the growing media. Mycorrhiza is a soil fungus that can symbiosis with the host plant's roots and has a broad influence on pathogenic microorganisms. Mycorrhiza can also increase secondary metabolites in plants.Â The compound which is the initial signal for plants to form secondary metabolites is salicylic acid. This research aimed to investigate effect mycorrhiza increase plant growth, the content of salicylic acid and reduce the attack of F. oxysporum fungi that cause Fusarium wilt in tobacco plants. This experiment used a completely randomized design with mycorrhiza dose treatment consisting of 6 treatments that are Control (Soil), M0 (AMB-P0K + 0 g polybag-1) M1 (AMB-P0K + 10 g polybag-1), M2 (AMB-P0K + 20 g polybag-1), M3 (AMB-P0K + 30 g polybag-1), M4 (AMB-P0K + 40 g polybag-1) with each treatment consisting of 5 replications. The results showed that AMB-P0K + mycorrhiza was significant at plant height, number of leaves, leaf area, disease index, pathogen incubation and SA contain.